Dietary Stress From Plant Secondary Metabolites Contributes to Grasshopper (Oedaleus asiaticus) Migration or Plague by Regulating Insect Insulin-Like Signaling Pathway - Li, Shuang; Huang, Xunbing; McNeill, Mark Richard; Liu, Wen; Tu, Xiongbing; Ma, Jingchuan; Lv, Shenjin; Zhang, Zehua (Frontiers in Physiology, 2019)
Diets essentially affect the ecological distribution of insects, and may contribute to or even accelerate pest plague outbreaks. The grasshopper, Oedaleus asiaticus B-Bienko (OA), is a persistent pest occurring in northern Asian grasslands. Migration and plague of this grasshopper is tightly related to two specific food plants, Stipa krylovii Roshev and Leymus chinensis (Trin.) Tzvel. However, how these diets regulate and contribute to plague is not clearly understood. Ecological studies have shown that L. chinensis is detrimental to OA growth due to the presence of high secondary metabolites, and that S. krylovii is beneficial because of the low levels of secondary metabolites. Moreover, in field habitats consisting mainly of these two grasses, OA density has negative correlation to high secondary metabolites and a positive correlation to nutrition content for high energy demand. These two grasses act as a ‘push-pull,’ thus enabling the grasshopper plague. Molecular analysis showed that gene expression and protein phosphorylation level of the IGF → FOXO cascade in the insulin-like signaling pathway (ILP) of OA negatively correlated to dietary secondary metabolites. High secondary metabolites in L. chinensis down-regulates the ILP pathway that generally is detrimental to insect survival and growth, and benefits insect detoxification with high energy cost. The changed ILP could explain the poor growth of grasshoppers and fewer distributions in the presence of L. chinensis. Plants can substantially affect grasshopper gene expression, protein function, growth, and ecological distribution. Down-regulation of grasshopper ILP due to diet stress caused by high secondary metabolites containing plants, such as L. chinensis, results in poor grasshopper growth and consequently drives grasshopper migration to preferable diet, such as S. krylovii, thus contributing to grasshopper plague outbreaks.